Walmart: a roadmap for globalisation - Gupta, Anil K. (Henry Stewart Talks, 2018)
This case study considers Walmart’s strategy for globalisation. Anticipating exhaustion of growth potential in its domestic market, Walmart looked to expand globally. In evaluating the ‘cost of delay’ it weighed the importance of: a) geographic proximity and cultural similarity to its home market and b) the greater potential for growth in emerging rather than developed markets. Did it make the right choices?